Digitalisasi Pelaporan Iuran Warga Berbasis Google Spreadsheet di Komplek Seroja Home Residence 2 - Irsan Herlandi Putra (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity aims to improve transparency and accountability in the management of citizen contributions through the implementation of a digital reporting system based on Google Spreadsheet in the Seroja Home Residence 2 Complex. The problems previously faced were the limitations of the manual system which was slow, inefficient, and less transparent. This activity was carried out through a series of stages, namely identifying needs, preparing system designs, training administrators and residents, and assisting with implementation. The results of the activity showed that the digital reporting system was able to improve administrative efficiency, strengthen citizen participation, and form an open and collaborative governance culture. This activity also increases digital literacy among residents and results in social change in the form of a shift in the role of residents from recipients of information to active partners in environmental management. This finding is reinforced by recent literature showing that simple yet participatory technology can be an innovative solution in strengthening local-based community governance. This activity can be replicated in similar environments with ongoing training and mentoring support.